But not all social media are the same: Analyzing organizations' social media usage patterns. Issue 1 (February 2016) - Go, Eun; You, Kyung Han
Highlights: Overall, the organizations use blogs most and virtual worlds least. The present study identified six clusters of organizations in regard to social media usage patterns. Organizations' strategies to combine social media can be categorized in three ways: visualization, virtualization, and interactive collaboration. Abstract: The present study explores how organizations use diverse social media applications for consumer relationship management. Based on a cluster analysis, the social media usage patterns of 317 organizations were analyzed. Six groups of organizations were identified in accordance with the social media applications predominantly used by each organization. The first three groups primarily used a single social media application (blogs, social networking sites, or widgets) to communicate with customers, whereas the second three groups employed multiple social media applications, often with an emphasis on visualization, virtualization, or interactive collaboration. In addition, this study found that organizations tend to use social media applications with two-way communication capabilities. The theoretical and practical implications of these findings are discussed in this paper.